2007
DOI: 10.1099/mic.0.2007/010751-0
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic adaptation of the halophilic fungus Hortaea werneckii: role of osmolytes and melanization

Abstract: This study was intended to determine the osmoadaptation strategy of Hortaea werneckii, an extremely salt-tolerant melanized ascomycetous fungus that can grow at 0-5.1 M NaCl. It has been shown previously that glycerol is the major compatible solute in actively growing H. werneckii. This study showed that the exponentially growing cells also contained erythritol, arabitol and mannitol at optimal growth salinities, but only glycerol and erythritol at maximal salinities. The latter two were both demonstrated to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(124 citation statements)
references
References 55 publications
9
106
0
2
Order By: Relevance
“…The polyols were extracted from 30 mg of freeze-dried cells using the previously described method (17). The cells were suspended in 500 l Bligh and Dyer solution (composed of methanol-chloroform-water [10: 5:4]) and vigorously shaken for approximately 30 min (IKA-Vibrax VXR; Janke & Kunkel).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polyols were extracted from 30 mg of freeze-dried cells using the previously described method (17). The cells were suspended in 500 l Bligh and Dyer solution (composed of methanol-chloroform-water [10: 5:4]) and vigorously shaken for approximately 30 min (IKA-Vibrax VXR; Janke & Kunkel).…”
Section: Methodsmentioning
confidence: 99%
“…The cultures of W. ichthyophaga for the analysis of intracellular compatible solutes after a hypo-osmotic shock were grown in triplicate in liquid YNB medium with 20% (wt/vol) NaCl (14,17). Hypo-osmotic shocks were performed as follows; the cells were grown in YNB with 20% NaCl to the mid-exponential growth phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been analysed in the salt sensitive yeast S. cerevisiae and in some halotolerant filamentous fungi; it was shown that mostly glycerol is accumulated upon increasing salt concentrations (Blomberg and Adler 1992). Glycerol is also the compatible solute found in highest concentrations in the halophilic black yeast H. werneckii (Kogej et al 2007). Other modifications upon exposure to high salt concentrations concern the microsomal HMG-CoA reductase (Vaupotic and Plemenitas 2007) and the glycerol-3-phosphate dehydrogenase (Lenassi et al 2011).…”
Section: Intracellular Adaptationsmentioning
confidence: 99%
“…Both the extremely halotolerant yeast Hortaea werneckii and the halophilic fungus Wallemia ichthyophaga accumulate glycerol to adapt to hyperosmotic conditions. The levels of glycerol are increased with increasing salinity and decreased after hy-poosmotic shock (51,52). Several genes known to be involved in glycerol production were found in the genomes of H. werneckii and W. ichthyophaga (53).…”
Section: Discussionmentioning
confidence: 97%